The effectiveness of interactive mobile health technologies in improving antenatal care service utilization in Dodoma region, Tanzania: A quasi—Experimental study - Theresia J. Masoi; Stephen M. Kibusi; Deogratius Bintabara; Athanase Lilungulu (PLOS Digital Health, 2023)
Antenatal care (ANC) provides a platform for important health care during pregnancy, including health promotion, screening, diagnosis and disease prevention. Timely and appropriate utilization of antenatal care can prevent complications as well as ensure optimal maternal and newborn health care. This study assessed the effectiveness of interactive (two way communication) mobile health technologies during antenatal period to improve maternal and newborn service utilization in Dodoma region, Tanzania. Using quasi-experimental design, participants were randomly selected to achieve a sample size of 450 pregnant women (Intervention = 150 and Control = 300) in Dodoma city from January to November, 2018. Interventions were matched to controls by gravidity, education level and gestational age at a ratio of 1 to 2. The intervention group received health education messages through their mobile phones, while the control group continued with standard antenatal care services offered in local clinics. Pregnant women were followed from their initial visit to the point of delivery. The Chi-square test was used to establish the association and regression analysis were used to test the effect of the intervention. The median age of participants was found to be 25 years that ranged from 16 to 41 years. Generally, 77.3 percent of participants in the intervention group utilized adequate (i. ANC care provided by skilled health personnel, ii. Sufficient number of ANC visits (4 or more visits during pregnancy), iii. Appropriate ANC contents provided (visits included at least 13 out of 15 of the recommended basic care procedures or contents) ANC services compared to 57.7 percent in the control group. Interactive mobile health technology system was observed to be effective on improving antenatal care service utilization (AOR = 2.164, P<0.05, 95% CI = 1.351–3.466) compared to conventional antenatal care health education given in local health facilities. Use of interactive mobile health technologies during antenatal period has the potential of improving access to information and antenatal care service utilization in the study setting. Trial Registration: PACTR202008834066796 “Retrospectively registered”. Author summary Increasing the utilization of maternal health care services is an important strategy to reduce preventable maternal morbidity and mortality. Each year, roughly a third of global maternal deaths are due to inadequate care during pregnancy. Antenatal care visits are ideal time to advice women and their families on essential pregnancy care and develop a birth plan and complications readiness. These approaches improve outcomes for women and may also reduce stillbirths and neonatal deaths. Improving maternal and neonatal health outcomes involves the provision and uptake of antenatal services that are timely (first visit during the first three months of pregnancy), sufficient (at least four antenatal visits) and adequate with appropriate contents. The use of mobile health interventions such interactive messaging system can provide behavioural support and health education needs to pregnant women. This study has demonstrated the importance of interactive mobile health technology in improving antenatal care service utilization compared to conventional method. The interactive mobile method raised awareness and served as the best alternative tool to provide health education among pregnant women. Consistent use of SMS technology to disseminate health information is a promising approach to improve monitoring of pregnant women and increase maternal health care service utilization.